Sustainable Waste Management Breakthrough: Transforming Plastic Waste into Eco-Friendly Briquette Charcoal - Dine Agustine; Mutia Amyranti; Nia Komalasari; Ira Rumiris Hutagalung; Ratih Kurniasari (Jurnal Presipitasi : Media Komunikasi dan Pengembangan Teknik Lingkungan, 2023)
Plastic waste has emerged as an important environmental concern. Among the various types of plastic waste, such as Polyethylene Terephthalate (PET) and Polypropylene (PP), these two contribute the most to the overall plastic waste problem need to be efficiently managed. The purpose of this research is to study the manufacture of briquettes from PET and PP plastic waste with the help of starch adhesive. This research is expected to reduce the negative impact of plastic waste. In this study, the data to be obtained were the calorific value of the briquettes, ash content, moisture content, volatile content and bound carbon content. The results show that the best raw material combination in terms of the calorific value of the resulting charcoal briquettes is the raw material mixture with the addition of PET. The results of the PET type plastic briquettes were superior with the results of the calorific value test of 10.129 cal/gram, the proximate test results of 3.11% ash content, 4.98% moisture content, 65.31% volatile matter content, and 78% bound carbon content 79%. While the PP type plastic briquettes obtained a calorific value test result of 9,949 cal/gram, the calorific value was lower than the PET type plastic briquettes.